Vatican Council II: More Postconciliar Documents (Vatican Collection II) - Mundadan, A M (Journal of Dharma, 1984)
Austin Flannery, O.P., ed. Vatican Council Il: More PostconciEiar Documents (Vatican tion 11) Grand Rapids, Michigan, W. M. B. Eerdman Publishing Co., 1982, Pp. xix +920. No price given.